Bridging the Gap: A Bibliometric Analysis of Differentiated Learning Research in Indonesia and Global Contexts - Nurjanah, Siti; Martaputri, Nurul Aulia; Febrian, Panca Ali; Sutrimo, Moh Slamet; Seran, D'aquinaldo Stefanus Fani (Universitas Negeri Semarang, 2024)
Implementing differentiated learning in Indonesia has several problems despite its vital role in improving educational quality. This study examines the disparity between research on differentiated learning in Indonesia and global research by doing a bibliometric analysis. The methodology utilizes bibliometric analysis of research literature on differentiated learning from the Scopus database. Data analysis involves examining research productivity, the extent of international collaboration, and the trends in research topics. The key findings suggest that although Indonesia has many writers contributing, its research has not achieved much global attention. In Indonesia, research primarily focuses on implementation within the context of national policies. However, global research has a broader reach, encompassing modern technology and an array of methodologies. These findings suggest that Indonesian researchers should broaden their research scope, enhance international collaborations, and investigate areas such as applying advanced technologies in customized education, the long-term effects on learning achievements, and creating tailored learning models suitable for the Indonesian context. As a policy recommendation, the government could offer targeted incentives to promote international research collaborations and establish online collaboration platforms to enhance cross-country cooperation in differentiated learning.